Snowmen all year - Buehner, Caralyn; Buehner, Mark (New York : Dial Books For Young Readers, 2010)
A child imagines what it would be like if a snowman, made of magical snow, could be a companion throughout the year.
Wilson's Children, September 2011.
School Library Journal, December 2010.
Publisher's Weekly, November 2010.
Horn Book, May 2011.
2.6
K-3
Keywords: Snowmen -- Fiction; Year -- Fiction; Stories in rhyme; Snowmen -- Juvenile fiction; Year -- Juvenile fiction